2011
DOI: 10.1007/s11746-011-1847-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Almond Cultivars by the Use of Thermal Analysis Techniques. Application to Cultivar Authenticity

Abstract: Almonds are subjected to thermal processes in the production of processed food and this can affect their thermal stability and lead to oxidation processes. In this work, almond samples from three different cultivars (Spanish Guara and Marcona, and American Butte) were characterized by using Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) at different heating rates. Crystallization and melting parameters were determined by DSC; whereas thermal stability was studied by TGA, showing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Good resolution among categories was achieved in all cases as shown by the low λ w values obtained. In particular, the application of DSC and related thermal properties, which was a novelty in the field of olive oil but was very recently and successfully utilized to discriminate food samples of different botanical origin 31, may be suitable for this purpose in combination with other techniques. Among thermal properties, those obtained from the deconvoluted peaks of transition (in particular peak 3 at the highest temperature of cooling transition) were more discriminant than those obtained by analysing the whole cooling profiles, confirming hypotheses from previous studies by the same authors 22.…”
Section: Discussionsupporting
confidence: 86%
“…Good resolution among categories was achieved in all cases as shown by the low λ w values obtained. In particular, the application of DSC and related thermal properties, which was a novelty in the field of olive oil but was very recently and successfully utilized to discriminate food samples of different botanical origin 31, may be suitable for this purpose in combination with other techniques. Among thermal properties, those obtained from the deconvoluted peaks of transition (in particular peak 3 at the highest temperature of cooling transition) were more discriminant than those obtained by analysing the whole cooling profiles, confirming hypotheses from previous studies by the same authors 22.…”
Section: Discussionsupporting
confidence: 86%
“…In general, AV tended to increase at 100 • C showing the formation of secondary oxidation products in accordance with the obtained PV values. Similar results were obtained in previous works with other nuts such as Spanish and American almond oils [27].…”
Section: Oxidative Indices: Pv and Avsupporting
confidence: 92%
“…Sunflower seed samples were directly analyzed by ATR-FTIR, HS-SPME-GC-MS, DSC, and TGA. For fatty acid composition and PV and AV determinations, the oil of samples was extracted by applying an analytical method previously developed [27]. Triplicates were carried out for all the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, this subject has received little attention, and very few studies can be found in the literature in which kinetic data are used to compare oxidative behaviors of different sorts of oils. In some of these studies isothermal differential scanning calorimetry data 19 and the Rancimat test have been used to characterize different vegetable oils. 20,21 In recent years, the number of virgin oils from different olive cultivars has grown enormously in supermarkets trying to highlight the better quality of olive oils from nutritional and culinary points of view.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nevertheless, this subject has received little attention, and very few studies can be found in the literature in which kinetic data are used to compare oxidative behaviors of different sorts of oils. In some of these studies isothermal differential scanning calorimetry data and the Rancimat test have been used to characterize different vegetable oils. , …”
Section: Introductionmentioning
confidence: 99%